PRINSIP TANGGUNG JAWAB TERBATAS DAN KEDUDUKAN PEMEGANG SAHAM SEBAGAI PENANGGUNG PAJAK - Alta Mahandara (Universitas Muhammadiyah Ponorogo, 2022)
In Limited Liability Company, as regulated in Article 3 Paragraph (1) of Limited Liability Company Law, there is limited liability principle for the Shareholder, whereas the Shareholder shall not be liable for the engagement and loss which bind/suffered by the company which exceeding what has been subscribed as shares. However, such limited liability principle is not adhered in taxation perspective, whereby by the issuance of the Ministry of Finance Regulation Number 189/PMK.03/2020 Tahun 2020, wherein the Shareholder of a Limited Liability Company is categorized as Tax Guarantor, which mean shall also be liable for the taxation obligation of such Limited Liability Company, including the Shareholder’s personal assets. Such obligation is direct obligation without preliminary basis which resulted in piercing the corporate veil action. Therefore, the author desire to analyse the contradiction between the categorization of Shareholder as Tax Guarantor as regulated in the Ministry of Finance Regulation Number 189/PMK.03/2020 Tahun 2020 with the limited liability principle as regulated in the Limited Liability Law. The research that is conducted to answer such question is a juridic-normative research, which is focussing on the implementation of the rules and norms in positive law. The author then found out that the categorization of Shareholders as Tax Guarantor shall re-assessed, because its contradict the limited liability principle of the Shareholder as regulated in the Limited Liability Company Law.